Universally designed public spaces by enhancing accessibility and connectivity - Abd. Samad, Nur Amirah; Said, Ismail; Abdul Rahim, Asiah (International Journal for Studies on Children, Women, Elderly And Disabled, 2018)
Public space, apart from public building is an important physical element in our built environment. Accessibility relates directly with the built environment and followed by accessible design that is often associated with providing to the needs of Persons with Disabilities (PwDs). The current realm of our built environment claims to be accessible but only restricted to new buildings of public attractions and high-rise skyscrapers erected at urban developments. The unprecedented and left out public spaces in between these developments are the victims. These public spaces are the paths, the links, the connections, the nodes and the transitions of our built environment. This paper emphasizes the importance of enhancing the accessibility and connectivity aspect in order to create a universally designed public space to have the expectation of seamless journey. Lack of seamlessness in the access route concludes that those public spaces have not been taken into consideration while designing or planning adjacent developments. Accessibility may have been provided but restricted and is not designed for all which eventually is essential for everyone to participate in social and communal life. Significantly, noting accessibility as a crucial key factor in ensuring social inclusion and creating a balanced social sustainability.